2016
DOI: 10.1016/j.jcm.2016.04.016
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological Role of Tumor Necrosis Factor in Human Immunity and Its Potential Implications in Spinal Manipulative Therapy: A Narrative Literature Review

Abstract: Objective: Although tumor necrosis factor (TNF) is a well-known inflammatory cytokine in the pathological development of various human diseases, its physiological roles are not widely understood nor appreciated. The molecular mechanisms underlying spinal manipulation therapy (SMT) remain elusive. The relationship between TNF and SMT is unclear. Thus, we performed this literature review to better understand TNF physiology and its potential relationship with SMT, and we propose a novel mechanism by which SMT may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…TNF is a pleiotropic cytokine increasingly recognized to regulate important physiological processes not only in the immune system, but also in the brain [ 9 , 10 , 11 ]. Evidence for TNF involvement in MS includes the identification of TNF in astrocytes, microglia, and endothelial cells, preferentially in acute and chronic active MS brain lesions and in the cerebrospinal fluid (CSF) of MS subjects [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…TNF is a pleiotropic cytokine increasingly recognized to regulate important physiological processes not only in the immune system, but also in the brain [ 9 , 10 , 11 ]. Evidence for TNF involvement in MS includes the identification of TNF in astrocytes, microglia, and endothelial cells, preferentially in acute and chronic active MS brain lesions and in the cerebrospinal fluid (CSF) of MS subjects [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that a possible explanation for of such contradictory data between these two studies [23,28] may be due to different methods in culture systems (i.e., incubation period) and doses of the inducer (i.e., endotoxin) [58].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that, in normal CNS sensitivity conditions, an increase of these signaling chemicals after SMT may lead to transient adverse effects (e.g., soreness, fatigue), whereas in circumstances of hyperexcitability, like in chronic pain states, such increase may drive to an escalation of events leading to pain exacerbation [58].…”
Section: Discussionmentioning
confidence: 99%
“…As with the keyword search term “cytokine” above, other unique keyword searches that directly relate to “immunity” such as interleukin and interferon are considered separately in more individual detail in the following sections. Twenty-seven references were identified in our search describing the relationship between chiropractic care and various aspects of immune function: 12 case studies, five research trials, and 10 reviews [ 85 , 93 , 96 , 122 - 145 ]. Of these original research studies meeting our inclusion/exclusion criteria, notable findings include one early set of pilot studies that report trends towards shifts in blood markers/CBCs in adjusted subjects [ 124 , 125 ], and another trial that reports lymphocytic activation in adjusted subjects as compared to control [ 132 ].…”
Section: Reviewmentioning
confidence: 99%